(Re)Membering: Black Women Engaging Memory through Journaling. (December 2022) - Smith, Dywanna; Kelly-Morris, Katelyn; Chapman, Shaniya
This manuscript is a confluence of voices: A Black university professor at a Historically Black University in the Southeast and her two pre-service teachers. Using journaling as a catalyst for transformative healing; three young, Black women discuss their intersecting identities and bear witness to each other's memories. To resist racist representations Black women must confront the colonizing ideology by developing a critical consciousness. In short, we must confront massive hate by fully loving and embracing our Blackness. The study elucidates how selfactualization writing can cultivate healing while promoting academic success.